Healthcare resource use and cost associated with timing of pharmacological treatment for major depressive disorder in the United States: a real-world study. (2nd December 2019) - McIntyre, Roger S.; Prieto, Rita; Schepman, Patricia; Yeh, Yu-Chen; Boucher, Matthieu; Shelbaya, Ahmed; Chambers, Richard; Gao, Xin; Pappadopulos, Elizabeth
Abstract: Background: Guidelines recommend selective serotonin reuptake inhibitors (SSRI) and serotonin norepinephrine reuptake inhibitors (SNRI) as first-line treatments for major depressive disorder (MDD) and emphasize the importance of early pharmacological treatment as key factors to treatment success. Objectives: To compare the MDD-related healthcare resource utilization (HCRU) and cost among patients (1) with early vs late pharmacological treatment initiation and (2) achieving minimum therapeutic dose (MTD) early vs late. Methods: The MarketScan database (2010–2015) was used. Adults who were newly-treated with SSRI/SNRI within 12 months after the initial MDD diagnosis (index) were included. Patients who initiated SSRI/SNRI within 2 weeks of the index date were defined as early initiators; those who reached MTD within 4 weeks of index date were defined as early MTD achievers. MDD-related HCRU and costs per year after the index date were compared between early and late initiators and between early and late achievers using propensity score matching and generalized linear models. Results: Of the 55, 539 patients, 60% were early initiators and 61% were early MTD achievers. The mean number of MDD-related outpatient visits per year were significantly higher for late initiator (6.7 vs 4.2, p < .001) and late MTD achievers (6.5 vs 4.5, p < .001) vs their early counterparts. Mean annual MDD-related outpatient, drug, and total cost were significantly higher for late initiators and MTD achievers vs the early groups. Conclusions: There is an opportunity to improve outcomes by treating MDD patients with SSRI/SNRI within 2 weeks and at or above the MTD within 4 weeks of diagnosis or less.